2021
DOI: 10.1111/cas.15072
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA just proximal to X‐inactive specific transcript facilitates aerobic glycolysis and temozolomide chemoresistance by promoting stability of PDK1 mRNA in an m6A‐dependent manner in glioblastoma multiforme cells

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution-NonCo mmercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…Additionally, upregulation of METTL3 in tumors increases adenylate kinase-4 expression to promote mitochondrial metabolism-mediated tamoxifen resistance and tumor progression [ 213 ]. Similarly, a m 6 A-dependent mechanism enhances PDK1 mRNA stability and mediates temozolomide chemoresistance in glioblastoma by inducing an increase in glycolysis [ 214 ]. The Warburg effect (tumor cell glycolysis) promotes release of glioma exosomes carrying circ_0072083 that upregulates NANOG expression by targeting miR-1252-5p and mediating m 6 A demethylation, thereby promoting temozolomide resistance [ 215 ].…”
Section: A Methylation Regulates the Biological Functions Of Tumor Cellsmentioning
confidence: 99%
“…Additionally, upregulation of METTL3 in tumors increases adenylate kinase-4 expression to promote mitochondrial metabolism-mediated tamoxifen resistance and tumor progression [ 213 ]. Similarly, a m 6 A-dependent mechanism enhances PDK1 mRNA stability and mediates temozolomide chemoresistance in glioblastoma by inducing an increase in glycolysis [ 214 ]. The Warburg effect (tumor cell glycolysis) promotes release of glioma exosomes carrying circ_0072083 that upregulates NANOG expression by targeting miR-1252-5p and mediating m 6 A demethylation, thereby promoting temozolomide resistance [ 215 ].…”
Section: A Methylation Regulates the Biological Functions Of Tumor Cellsmentioning
confidence: 99%
“…In Glioblastoma (GBM), Li et al recently showed that long noncoding RNA just proximal to X-inactive specific transcript (JPX) interacted with N6-methyladenosine (m 6 A) demethylase FTO and enhanced FTO-mediated PDK1 mRNA demethylation. Additionally, JPX exerted its GBM-promotion effects through the FTO/PDK1 axis (Li et al, 2021). These outcomes reveal the critical role of JPX in promoting GBM aerobic glycolysis-m 6 A demethylase FTO.…”
Section: A Regulates Cancer Metabolismmentioning
confidence: 81%
“…Currently, Li and collaborators demonstrated that the JPX/FTO/ PDK1 axis could facilitate aerobic glycolysis in GBM cells, which was correlated with GBM cells' sensitivity to temozolomide (TMZ). These findings provide valuable information for understanding that blocking the JPX/FTO/PDK1 axis may serve as a promising strategy for mitigating the efficacy of TMZ in GBM (Li et al, 2021). By elucidating the biological roles of m 6 A's modification in natural killer (NK) cells, Ma and collaborators uncovered a new direction for harnessing NK Cell antitumor immunity.…”
Section: Potential Clinical Applications Of M 6 a And Targeting The M...mentioning
confidence: 98%
“…In addition to these classic metabolic enzymes in glycolysis, m6A modification can also regulate some proteins related to glucose metabolism to participate in tumor progression. In GBM, as for temozolomide chemoresistance, JPX can promote the stability of PDK1 through m6A-dependent manner of FTO, thus promoting aerobic glycolysis and promote chemoresistance [ 133 ]. In cervical cancer and liver cancer, PDK4 is involved in glycolysis and ATP generation.…”
Section: The M6a and Metabolicmentioning
confidence: 99%